Competition between quasi-planar and cage-like structures in the B29−cluster: photoelectron spectroscopy and ab initio calculations - Li, Hai-Ru; Jian, Tian; Li, Wei-Li; Miao, Chang-Qing; Wang, Ying-Jin; Chen, Qiang; Luo, Xue-Mei; Wang, Kang; Zhai, Hua-Jin; Li, Si-Dian; Wang, Lai-Sheng (Physical Chemistry Chemical Physics, 2016)
Size-selected boron clusters have been found to be predominantly planar or quasi-planar (2D) in the small size regime with the appearance of three-dimensional (3D) borospherene cages of larger sizes. A seashell-like B28- cluster was previously shown to be the smallest borospherene, which competes with a quasi-planar isomer for the global minimum. Here we report a study on the structures and bonding of the B29- and B29 clusters using photoelectron spectroscopy (PES) and first-principles calculations and demonstrate the continued competition between the 2D and borospherene structures. The PES spectrum of B29- displays a complex pattern with evidence of low-lying isomers. Global-minimum searches and extensive theoretical calculations revealed a complicated potential energy surface for B29- with five low-lying isomers, among which the lowest three were shown to contribute to the experimental spectrum. A 3D seashell-like Cs (2, 1A') isomer, featuring two heptagons on the waist and one octagon at the bottom, is the global minimum for B29-, followed by a 2D C1 (3, 1A) isomer with a hexagonal hole and a stingray-shaped 2D Cs (1, 1A') isomer with a pentagonal hole. However, by taking into account the entropic effects, the stingray-shaped isomer 1 was shown to be the lowest in energy at room temperature and was found to dominate the PES spectrum. Isomers 2 and 3, which have lower electron binding energies, were also found to be present in the experiment. Chemical bonding analyses showed that isomer 1 is an all-boron analogue of benzo[ghi]fluoranthene (C18H10), whereas the borospherene isomer 2 possesses 18π electrons, conforming to the 2(N + 1)2 electron counting rule for spherical aromaticity. For the B29 neutral cluster, the seashell-like borospherene isomer is the global minimum, significantly lower in energy than the stingray-shaped quasi-planar structure.Size-selected boron clusters have been found to be predominantly planar or quasi-planar (2D) in the small size regime with the appearance of three-dimensional (3D) borospherene cages of larger sizes. A seashell-like B28- cluster was previously shown to be the smallest borospherene, which competes with a quasi-planar isomer for the global minimum. Here we report a study on the structures and bonding of the B29- and B29 clusters using photoelectron spectroscopy (PES) and first-principles calculations and demonstrate the continued competition between the 2D and borospherene structures. The PES spectrum of B29- displays a complex pattern with evidence of low-lying isomers. Global-minimum searches and extensive theoretical calculations revealed a complicated potential energy surface for B29- with five low-lying isomers, among which the lowest three were shown to contribute to the experimental spectrum. A 3D seashell-like Cs (2, 1A') isomer, featuring two heptagons on the waist and one octagon at the bottom, is the global minimum for B29-, followed by a 2D C1 (3, 1A) isomer with a hexagonal hole and a stingray-shaped 2D Cs (1, 1A') isomer with a pentagonal hole. However, by taking into account the entropic effects, the stingray-shaped isomer 1 was shown to be the lowest in energy at room temperature and was found to dominate the PES spectrum. Isomers 2 and 3, which have lower electron binding energies, were also found to be present in the experiment. Chemical bonding analyses showed that isomer 1 is an all-boron analogue of benzo[ghi]fluoranthene (C18H10), whereas the borospherene isomer 2 possesses 18π electrons, conforming to the 2(N + 1)2 electron counting rule for spherical aromaticity. For the B29 neutral cluster, the seashell-like borospherene isomer is the global minimum, significantly lower in energy than the stingray-shaped quasi-planar structure.